GAMBARAN KUALITAS BAKTERIOLOGIS AIR SUMUR GALI DI WILAYAH KERJA PUSKESMAS PENGASIH 1 KABUPATEN KULON PROGO - Alya Nida Tahera Mahardika; Mursid Rahardjo; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
Dug wells is one of the most source of fresh water that used by people who live in Pengasih 1 Health Center Work Area. Water of dug wells is the shallow groundwater that easily contaminated by the contaminants on the ground. The puspose of this study is to describe the water bacterial quality of dug wells associated with the distance of dug wells with the source of contaminant. This study is observational descriptive with cross sectional design. The contaminant that measured in this study is the distance between dug well with septic tank, sewerage, and other contaminants (cattle pen or landfill). Water bacterial quality measured using MPN coliform. The number of sample in this study is 42 wells. Not eligible distance between wells and septic tank is 47,6%, wells and sewerage is 76,2%, wells and other contaminants is 76,2%. Overall the distance between dug wells and contaminant sources that not eligible is 92,9%. The bacterial quality of water is 100% not eligible. The conclusion of this study is most of the wells is not eligible with the distances of contaminant sources and all wells is not eligible in water bacterial quality.